Diabetes aggravates myocardial ischaemia reperfusion injury via activating Nox2‐related programmed cell death in an AMPK‐dependent manner. Issue 12 (29th April 2020) - Wang, Chunyan; Zhu, Lijie; Yuan, Wenlin; Sun, Lingbin; Xia, Zhengyuan; Zhang, Zhongjun; Yao, Weifeng
Abstract: Cardiovascular diseases such as myocardial ischaemia have a high fatality rate in patients with diabetes. This study was designed to expose the crosstalk between oxidative stress and AMPK, a vital molecule that controls biological energy metabolism, in myocardial ischaemia reperfusion injury (I/RI) in diabetic rats. Diabetes was stimulated in rats using streptozotocin injection. Rats were separated on random into control, control + I/R, Diabetes, Diabetes + I/R, Diabetes + I/R + N‐acetylcysteine and Diabetes + I/R + Vas2870 groups. Myocardial infarct size was determined, and the predominant Nox family isoforms were analysed. In vitro, the H9C2 cells were administered excess glucose and exposed to hypoxia/reoxygenation to mimic diabetes and I/R. The AMPK siRNA or AICAR was used to inhibit or activate AMPK expression in H9C2 cells, respectively. Then, myocardial oxidative stress and programmed cell death were measured. Diabetes or high glucose levels were found to aggravate myocardial I/RI or hypoxia/reoxygenation in H9C2 cells, as demonstrated by an increase in myocardial infarct size or lactate dehydrogenase levels, oxidative stress generation and induction of programmed cell death. In diabetic rat hearts, cardiac Nox1, Nox2 and Nox4 were all heightened. The suppression of Nox2 expression using Vas2870 or Nox2‐siRNA treatment in vivo or in vitro, respectively, protected diabetic rats from myocardial I/RI. AMPK gene knockout increased Nox2 protein expression while AMPK agonist decreased Nox2 expression. Therefore, diabetes aggravates myocardial I/RI by generating of Nox2‐associated oxidative stress in an AMPK‐dependent manner, which led to the induction of programmed cell death such as apoptosis, pyroptosis and ferroptosis.